Integrasi Teknologi dan Nilai-Nilai Islami dalam Strategi Pembelajaran PAI di Era Disrupsi - Neni, Neni; Handayani, Satri; Basori, Basori (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
This study explores the integration of technology in Islamic Religious Education (PAI) as a strategic response to the challenges of the digital disruption era, aiming to strengthen the internalization of Islamic values among students. Using a descriptive qualitative approach through literature review and document analysis, the study found that PAI teachers have begun implementing various innovations such as the use of digital media, technology-based learning projects, and gamification to create more engaging and meaningful learning experiences. The findings show that digital media not only serves as a visual aid but also functions as an effective tool for fostering students’ Islamic character in a contextual manner. Data analysis reveals alignment with social constructivist and character education theories, emphasizing the importance of collaboration among teachers, parents, and the community. Despite challenges such as limited infrastructure and digital literacy, technological integration remains a strategic solution for shaping a generation of Muslims who are religious, critical, and adaptive to contemporary developments. This study recommends teacher training, supportive policies, and further research to evaluate the practical impact of these integrative strategies in real classroom settings.